Mapping Global and Regional Value Chains in SACU : Sector-Level Overviews - World Bank Group (World Bank, Washington, DC, 2016)
In considering the prospects for expanding non-commodities exports, the SACU region faces a global environment that has changed markedly over the past two decades. First, trade is increasingly shifting away from high income countries and toward developing countries. Second and perhaps most importantly, is the increasing importance of or ‘global production networks’ or ‘global value chains’ (GVCs). With wages rising rapidly in China and other places where GVC-oriented trade is concentrated, parts of these value chains are migrating to new global locations. Some estimates indicate that over the next generation 85 million manufacturing jobs will migrate from coastal China, and Sub-Saharan Africa is expected to be a major beneficiary. The SACU region, with its abundance of natural capital and surplus labor, along with a relatively high quality infrastructure and institutional environment, should be in a good position to attract investment and create a ‘factory Southern Africa’. Beyond assembly manufacturing that is typical of GVCs (e.g. apparel, electronics, automotive), the region should also be well-placed to compete as a location for value-addition to agricultural and mineral commodities (‘beneficiation’). Both types of investment would not only drive exports and have the potential to create significant employment, but also support upgrading by accessing global technologies and knowledge. And with growing markets across Africa, a ‘factory Southern Africa’ might increasingly be sustainable in the regional context.